Identifiying effective coping skills and protective factors among resilient Malay Muslim women with histories of sexual abuse - Lekganya, Is-haaq (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
The current study provides understanding about the inner traumatic experiences of Muslim women with histories of sexual abuse. It also explores and identifies effective coping skills and protective factors that lead to resilience among Muslim women survivors of sexual abuse. Five participants fulfilling resilience criteria were recruited for the study. Using a case study research approach, the findings of this study reveal that at first, these survivors faced psychological complications portrayed by feelings of self-hatred, loss of confidence, constant fears, incapacitating flashbacks and overwhelming suicidal ideation. Some experienced unjustified interpersonal reactions characterized by isolation, rejection and humiliation. These survivors were able to achieve resilience through perceiving their challenges as a Ḥikmah and a test from Allah. Their belief in the Akhirah safeguarded them from committing suicide or engaging in harmful behaviours associated with the abuse. Through Ḥalaqah or Tadhkirah, they were able to learn how to use the teachings of the Qur'an and Sunnah to understand, accept and cope with the abuse. An Ustādhah emerged to be an important supportive figure for all the participants. They effectively coped with their devastating feelings by emerging with a sense of optimism and assertiveness. They also engaged in recreational activities and knowledge or skills acquisition. Their effective coping skills are summed up in five elements; 1) Attitudes of optimism and assertiveness, 2) Ḥikmah and positive affirmations, 3) Positive life experiences and opportunities, 4) Leading life according to the Qur'ān and Sunnah, and 5) Engaging in Ibadah. Their protective factors are made up of five elements; 1) Firm belief and trust in Allah, 2) Belief in Akhirah, 3) Supportive relationships from an Ustadhah and others, 4) Participating in Ḥalaqah and Tadhkirah, and 5) Recitation and memorization of Qur'an with understanding and acceptance. As a result of all these skills and factors, the survivors were able to achieve resilience and therefore lead satisfying and productive lives again. Findings of this study provide more clinical utility and ways to conduct efficient psychotherapy for Muslim survivors of sexual abuse.